A homozygous frameshift variant in an alternatively spliced exon of DLG5 causes hydrocephalus and renal dysplasia. Issue 5 (21st February 2019) - Yüksel, Zafer; Vogel, Florian; Alhashem, Amal M.; Alanzi, Talal S.A.; Tabarki, Brahim; Kampe, Kapil; Kandaswamy, Krishna K.; Werber, Martin; Bertoli‐Avella, Aida M.; Beetz, Christian; Rolfs, Arndt; Bauer, Peter
Abstract :